Performance of elite cowpea (vigna unguiculata) genotypes at Mankweng and Bela-Bela, Limpopo Province - Sekgobela, Molebjane Marry (My University, 2019)
Cowpea (Vigna unguiculata) is a multi-purpose crop as it can be used for human consumption and livestock feeding. Cowpea serves as one of the cheapest sources of vegetable protein as the dry grain contains 25-30% protein. Its ability to tolerate drought and fix atmospheric nitrogen makes it suitable for marginal areas with low rainfall and poor soil fertility. However, low cowpea yields are common in Limpopo province due to shortage of improved varieties and lack of good seed for planting. The objectives of the present study were to determine growth, yield components and grain yield of elite cowpea genotypes across two locations and seasons, and to determine grain yield and yield components stability of the elite cowpea genotypes across the environments. The experiments were conducted at the University of Limpopo Experimental farm (Syferkuil) in Mankweng and Towoomba Research Station located in Bela-Bela, Limpopo Province during 2015/16 and 2016/17 growing seasons. The trials were carried out in a randomized complete block design (RCBD) consisting of three replications. Ten elite cowpea breeding lines (L1-L10) and a control check Bechuana White (BW) were planted at inter-row and intra-row spacings of 1 m and 0.3 m, respectively, in two rows of 6 m length. Round-up (isopropylamine salt of glyphosate) and Dual (S-metalachlor) at the rate of 3 L/ha and 0.5 L/ha, respectively, were used to control weeds at planting. Insecticide Karate (lambda-cyhalothrin) and Aphox (pirimicarb) at the rate of 1 L/ha and 500 g/ha were applied to control aphids, pod borers and other insects. Initial soil sampling was done at the depth of 0-20 cm to determine soil pH, organic matter, nitrate, ammonium, phosphorus and soil particle size. Agronomic data collected included number days to 50% flowering, number of days to 90% maturity, canopy width, plant height, peduncle length, number of pods per plant, pod length, hundred seed weight, fodder and grain yield. The collected data were subjected to analysis of variance using SAS software to determine the performance of the cowpea genotypes across the two locations and seasons. Means showing significant differences were separated using Duncan Multiple Range Test at the probability level of 5%. Data for number of days to 90% maturity, grain and fodder yields were further subjected to stability analysis through GGE biplot using Genstat software application. The results showed statistical differences for most of the studied traits as affected by genotype, location, seasonal effects and their interactions. Among the genotypes, average number of days to 50% flowering ranged from 53 to 60 days, while number of days to 90% maturity ranged from 89 to 96 days, with line L9 being the earliest to flower and mature. Tall plants were given by Line L5 (48.94 cm), followed by L7 (48.72 cm) and L10 (48.35 cm). Breeding line L7 recorded long peduncles with a mean of 36.37 cm. Number of pods per plant had a range of 16.00 to 25.52, while pod length varied from 14.46 to 17.63 cm, with line L7 having the highest number of pods per plant with long pods. Line L3 produced least number of pods per plant and shorter pods. Local check BW produced more number of seeds per pod as compared to all the breeding lines with a mean of 12.89 seeds/pod. One hundred seed weight varied from 15.67 g to 22.70 g among the genotypes. Grain yield among the genotypes ranged from 1441.20 to 2595.20 kg/ha with the best yielder being line L7, which was followed by line L2 (1928.00 kg/ha), L10 (1891.70 kg/ha) and Local variety BW (1858.70 kg/ha). The least grain yield was observed for line L8. Among the locations, Towoomba had significantly higher grain yield than Syferkuil with mean values of 1604.20 and 1982.20 kg/ha respectively. Significantly higher grain yield was recorded in 2016/17 season with a mean value of 1854.80 kg/ha than 2015/16 season (1732.30 kg/ha). Fodder yield ranged from 1934.20 to 3611.00 kg/ha, with line L3 being the highest yielder and it was followed by line L10 with an average of 3022.00 kg/ha. Local check BW produced the least fodder yields. The GGE biplot showed that lines L2, L9 and L4 matured earlier than all other lines including local variety BW and were stable across locations and seasons in terms of maturity. The biplot identified breeding lines L7, L2, L10 and Local check BW as the highest grain yielders but only line L7 and L2 were stable across the two locations and seasons. Lines L4, L10, L3, and L2 were the highest fodder yielders but only line L2 was stable across locations and seasons. Therefore, breeding lines L7 and L2 are recommended for both grain and fodder yield in both locations. Key words: cowpea, elite, breeding line, location, seasons, grain yield and stability.
Thesis (M. Sc. Agriculture (Agronomy)) -- University of Limpopo, 2019
Keywords: Cowpea; Elite; Breeding line; Location; Seasons; Grain yield; Stability; Cowpea; Animal feeding